2009
DOI: 10.2105/ajph.2008.135319
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Physical Environment and Sociodemographic Characteristics on Children's Mode of Travel to and From School

Abstract: Objectives. We examined whether certain characteristics of the social and physical environment influence a child's mode of travel between home and school. Methods. Students aged 11 to 13 years from 21 schools throughout London, Ontario, answered questions from a travel behavior survey. A geographic information system linked survey responses for 614 students who lived within 1 mile of school to data on social and physical characteristics of environments around the home and school. Logistic regression analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
264
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 322 publications
(308 citation statements)
references
References 40 publications
24
264
0
4
Order By: Relevance
“…But when it comes to effective travel mode choice, girls are far more driven to different places then boys. This gendered result has also been found by Brown et al (2008), Rodriguez and Vogt (2009) and Larsen et al (2009).…”
Section: <Insert Figure 1 Here>supporting
confidence: 84%
“…But when it comes to effective travel mode choice, girls are far more driven to different places then boys. This gendered result has also been found by Brown et al (2008), Rodriguez and Vogt (2009) and Larsen et al (2009).…”
Section: <Insert Figure 1 Here>supporting
confidence: 84%
“…20,29,47,48 Our study adds to this literature by investigating such associations in a population of young children from low-income Values shown are regression coefficients (95% confidence intervals) for standardized environmental variables (rescaled, standard deviation=1); area characteristics are for neighborhood buffers, drawn as 0.5 km buffers around a line between the child's home and school; all models were adjusted for characteristics of the child (age, sex, and race/ethnicity), mother (age, born outside of the USA, use of Spanish, employed/student status), household (number of rooms), all of the neighborhood characteristics listed, and, for physical activity only, the total number of hours recorded as awake and the time of year; bold font is used to indicate statistical significance (p≤0.05); N=428 families. While previous studies have reported correlations between land use mix, 49,50 subway stop density, 51 safety, 21,24,25,27 vegetation, 30 or parks 31,32 with youth physical activity or adiposity, our results examine these associations in a highrisk urban subgroup with detailed outcome measurement using accelerometry and anthropometry. In this cohort of preschool-age children from low-income families in New York City, several measures of neighborhood composition, walkability, pedestrian safety, and greenness were correlated with physical activity or adiposity.…”
Section: Discussionmentioning
confidence: 84%
“…Mixed land use was calculated by using an entropy index, which ranges from 0 (single land use) to 1 (equal distribution of residential, commercial, industrial, institutional, and vacant land classifications). 23,24 Site Audits School level design variables were obtained from site audits conducted by the observers during school drop-off time. Only adults employed by Toronto Police Services surrounding the school were identified as school crossing guards.…”
Section: Municipal Property Assessment Corporationmentioning
confidence: 99%